Minifamosos nas redes sociais: o vazio, os excessos e os enlaces do sujeito - Vaz, Andrea Cristiane (2016)
This research aims to study the mini famous in social networks, their links, paradoxes and contradictions in relation to the subject’s desire, symbolic and imaginary constitution. Psychoanalysis is applied to investigate the discourse of contemporary social imaginary of fame through Facebook. Its focus is on analyzing the site as a social visibility and identity construction instrument, and highlight its mechanisms as means of access to modes of subjectivity in celebrity culture. It Intends to discuss and assert psychoanalysis function in this context. It presents a theoretical articulation of several authors of psychoanalysis, focusing on the approaches of Freud and Lacan, and scholars of contemporary culture. Among the topics covered are: the symbolic decline; the function of desire and the dichotomies between the imaginary feeling of excess and emptiness; the concepts interventions on this process as narcissism, semblance, fetish and envy, especially in the basic processes of constitution of the subject, such as recognition and identity. Based on the psychoanalytic investigation of Facebook, we conclude: the site offers the possibility for the subject to give himself a new name and then, to be recognized; likewise, it is a renewal of identity tool; we become mini famous in our online network, we acquire the same characteristics and the exact behavior of celebrities; by means of our profile picture we make a famous semblance, and it shows we live in the celebrity culture; we are a fetish object to the other; the site is used as a mirror for us to obtain narcissistic recognition and at the same time it encourages the comparison and envy; social networks make semblance of social bond and therefore diminish the distress of loneliness; the recognition obtained through Facebook is an attempt to fill the void of meaning; narcissism on the social networks is a way of behavior in which the jouissance excesses appear; being a mini famous on Facebook suggests a form of jouissance that would come from an inconsistency of the symbolic in our culture; the psychoanalysis function is to elucidate the cultural mechanisms that connect the subject in the discourse of the Other, trapping him in the imaginary, as they disable the subject of meaning his jouissance and being the subject of his own desire